Modelling of Factors Correlated with the Umrah Performing Trend Among Middle Class Malaysian Muslims - Hasan, Ahmad; M. R., Abdul Hamid (2012)
INTRODUCTION P1. Observation confirms that there is a steady increasing number of middle class Malaysian muslims performing umrah for the second time and so forth even though performing umrah is the one-off obligation in Islamic worship. P2. Since the trend is continuing, there must be rock solid reasons behind the scenario which are worthy of examination. P3. This survey research attempts to gauge the trend through pre-determined contributing factors as suggested by the number of references (jawhar.gov.my) namely financial capability, spiritual reasons, business opportunity, religious self-purification and godly aspired visit. P4. The finding will path away toward the establishment of 1Malaysia Islamaic Endowment Fund